GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 682 species occurrences available in GBIF matching the query: Geometry: POLYGON((-43.16322 -23.03172,-43.18382 -23.01528,-43.20168 -23.01276,-43.21815 -23.02034,-43.22365 -23.04814,-43.21815 -23.0671,-43.19069 -23.08984,-43.16734 -23.07847,-43.13988 -23.07594,-43.13026 -23.05699,-43.16322 -23.03172)) or POLYGON((-43.15876 -22.97167,-43.1464 -22.97546,-43.13473 -22.96282,-43.14022 -22.92867,-43.15876 -22.86858,-43.12855 -22.83188,-43.11001 -22.80277,-43.09628 -22.77365,-43.09353 -22.75782,-43.0949 -22.74199,-43.11893 -22.74199,-43.13885 -22.74579,-43.15601 -22.75592,-43.13404 -22.76985,-43.14983 -22.81923,-43.16631 -22.84454,-43.19721 -22.85403,-43.16288 -22.88566,-43.15533 -22.90401,-43.15052 -22.92551,-43.14434 -22.94512,-43.15052 -22.95713,-43.15876 -22.97167)) or POLYGON((-43.78532 -22.94195,-43.82103 -22.94828,-43.86223 -22.97736,-43.85262 -23.01528,-43.81554 -23.05573,-43.77708 -23.10373,-43.66173 -23.08858,-43.59718 -23.06962,-43.61641 -23.02287,-43.78532 -22.94195)) HasGeospatialIssue: false. The dataset includes 682 records from 32 constituent datasets: 2 records from iNaturalist Research-grade Observations. 2 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 21 records from The New York Botanical Garden Herbarium (NY). 259 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Distribution ashore and breeding places of southern elephant seals. 8 records from Geographically tagged INSDC sequences. 86 records from CAS Ichthyology (ICH). 2 records from SOMBASE BIOCONSTRUCTORS. 1 records from Queensland Museum provider for OZCAM. 2 records from Tropicos Specimen Data. 6 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 154 records from Mollusca Collection - Museu Nacional/UFRJ. 48 records from EOD - eBird Observation Dataset. 1 records from Collection Crustacea - ZMB. 1 records from MBML-Herbario - Herbário Mello Leitão. 2 records from Museum of Comparative Zoology, Harvard University. 4 records from MBM - Herbário do Museu Botânico Municipal. 2 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 1 records from Projeto Abrace o Boto Cinza. 1 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 26 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 1 records from Coleção de Aves do Museu Nacional / UFRJ. 1 records from MVZ Bird Collection (Arctos). 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2 records from A global database for the distributions of crop wild relatives. 3 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 10 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 25 records from Diveboard - Scuba diving citizen science observations. 3 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from CONN. 4 records from Natural History Museum (London) Collection Specimens. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences